Labour market effects of retraining for the unemployed: The role of occupations - Thomas Kruppe; Julia Lang (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
We analyse the impact of retraining for the unemployed on future labour market success, and estimate effects separately for different target occupations. We use German registry data and apply statistical matching methods. The results show that on average, after a period with strong lock-in effects, retraining increases the employment probability of women by more than 20 percentage points. Effects for male participants are somewhat weaker. Although we find differences in the effectiveness of retraining by target occupations, these differences cannot completely explain the observed gender differences. Healthcare occupations, which are the most important target occupations especially of female participants, are among those with the strongest effects. Despite differences between occupational fields, retraining in most of the considered occupations positively affects employment prospects of participants. Finally, sorting into different occupations seems to be present, as participants with different target professions also differ in their observable characteristics. – – In diesem Papier untersuchen wir die Wirkung von Weiterbildungen mit Abschluss in einem anerkannten Ausbildungsberuf (Umschulungen) unter Berücksichtigung unterschiedlicher Zielberufe der Teilnehmer. Dafür nutzen wir Prozessdaten der BA und verwenden Matchingmethoden. Die Ergebnisse zeigen, dass Umschulungen nach einer Periode mit starken Lock-in Effekten die Beschäftigungswahrscheinlichkeit für weibliche Teilnehmer um mehr als 20 Prozentpunkte erhöhen. Für Männer sind die Effekte etwas niedriger. Außerdem unterscheiden sich die Effekte je nach Zielberuf, auch wenn eine Umschulung sich für fast alle betrachteten Berufsfelder positiv auf die Beschäftigungschancen der Teilnehmer auswirkt. Gesundheitsberufe, die insbesondere für Frauen die bedeutendste Berufsgruppe darstellen, gehören zu den Berufen mit den stärksten positiven Effekten. Allerdings können Unterschiede nach Berufen die Unterschiede in den Effekten zwischen Männern und Frauen nicht vollständig erklären. Zudem zeigt die Untersuchung, dass sich Teilnehmer mit unterschiedlichen Zielberufen auch in ihren beobachtbaren Eigenschaften unterscheiden.
Keywords: J24; J68; C14; 330; Evaluation of active labour market policies; retraining; occupations